(untitled) (Dhaka University Journal of Biological Sciences, 2018)
Karyomorphological features of Justicia adhatoda L. were investigated in this study after differential staining with orcein, CMA and DAPI for proper characterization. In this species "Simple Chromocenter Type" of interphase nuclei was observed with many small heterochromatin blocks after orcein staining. Prophase chromosomes showed "Interstitial Type" of staining pattern which indicated the tendency of aggregation of heterochromatin in interstitial regions of chromosome. This species was found to possess 2n = 34 metacentric chromosomes. The total length of 2n chromosome complement was 132.17 μm. Individual chromosome length ranged from 2.57 to 5.43 μm. The relative length of each chromosome ranged from 0.02 to 0.04. A total of seven CMA-positive bands were observed in this species whereas no band was found after DAPIstaining. This result suggested the absence of AT-rich portions and occurrence of GC-rich portions in the respective banded chromosomes. Except 2n chromosome number, the other karyological and fluorescent banding information probably was the first report for this species and it might help to enhance the chromosomal data base with detailed karyomorphological information of this plant species in Bangladesh. Dhaka Univ. J. Biol. Sci. 27(2): 175-181, 2018 (July)